The description, measurement with inter‐ and intra‐observer reliability of calcaneal tunnel placement for tendon transfer in Achilles tendon reconstruction - Michael R. Carmont; Tor Kristian Andresen; Fraser Morgan; Katarina Nilsson‐Helander; Elisabeth Ellingsen Husebye (Journal of Experimental Orthopaedics, 2025)
Abstract Purpose A tendon transfer is a common method of treating ankle plantar flexion weakness and tendon end non‐union following chronic Achilles tendon rupture and delayed representation following Achilles tendon re‐rupture. Commonly, the transferred tendon is fixed into a bone tunnel on the postero‐superior surface of the calcaneum close to the distal Achilles tendon insertion. To date, there is no standardised description or measurement of calcaneal tunnel position. The aim of this study is to describe the anatomic location for calcaneal tunnel placement and to determine the reliability of a method of measuring tunnel position and direction within the calcaneum. Methods The routine post‐operative lateral ankle radiographs from 40 patients (40 ft) following Achilles tendon reconstruction using tendon transfer into the calcaneum: calcaneal tunnel zone (CTZ), calcaneal tunnel ratio (CTR) and calcaneal tunnel angle (CTA) were tested for reliability using test‐retest between three observers. Additionally, CTR and CTA were compared in cases where a calcaneoplasty was performed or not. Results The intraclass correlation coefficient (ICC) of the CTR and CTA was found to be 0.86–0.95 (95% confidence interval [CI]: 0.75‐0.98) and 0.95–0.99 (95% CI: 0.92–0.99), respectively, indicating good and excellent reliability. Patients who received a calcaneoplasty had a significantly greater CTR of 0.74 (0.1) and a lower CTA of 76.1° (10.8) compared to those who did not have a CTR of 0.61 (0.1) and 100.9 (12.4), Diff 95% CI: 0.13 (0.08–0.18) and −25 (−32 to −17), respectively, both p < 0.001. Conclusions The CTR and CTA were reliable measures for the calcaneal tunnel following Achilles tendon reconstruction using tendon transfer within the limitations of the sagittal radiographic view. When a calcaneoplasty was performed, it resulted in a significantly greater CTR. These measurements should be used to describe calcaneal tunnels rather than a description of tunnel placement to optimise predictive factors following Achilles tendon reconstruction. Level of Evidence Level III.